Anti-pollution wearable sweat sensor based on phase transition protein complex hydrogel and its preparation method and application

By modifying the phase-transformation protein complex hydrogel on the screen-printed electrode of the wearable sweat sensor, the problem of insufficient sensor flexibility, anti-pollution and electrocatalytic performance is solved, and high sensitivity and accuracy dopamine detection is achieved.

CN118592895BActive Publication Date: 2025-02-11QINGDAO UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410680333.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-02-11
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

Existing wearable sweat sensors have problems such as insufficient flexibility and self-healing ability, poor anti-pollution and antibacterial properties, and poor conductivity and electrocatalytic performance, resulting in low detection accuracy and sensitivity.

Method used

Using an anti-pollution wearable sweat sensor based on phase-transformation protein complex hydrogel, the A-BSA-MX-CeO2 hydrogel is modified on screen-printed electrodes to improve the flexibility, anti-pollution, antibacterial and electrocatalytic properties of the sensor. .

Benefits of technology

The flexibility and self-healing ability of the sensor are realized, which significantly improves anti-pollution and antibacterial properties, enhances conductivity and electrocatalytic properties, and improves the detection sensitivity and accuracy of dopamine in sweat.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118592895B_ABST
    Figure CN118592895B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of electrochemical detection technology, and discloses an anti-pollution wearable sweat sensor based on a phase transition protein complex hydrogel, and a preparation method and application thereof. By modifying the phase transition protein complex hydrogel with antibacterial-anti-pollution-electrocatalytic properties prepared by the present invention onto a flexible printed electrode integrated with a sweat-stimulated ion introduction electrode, an anti-pollution electrochemical sensor that can be directly used for the detection of dopamine in sweat is constructed. The composite hydrogel disclosed by the present invention has excellent antibacterial, anti-pollution and electrocatalytic properties; the constructed anti-pollution wearable sweat sensor can be used for the direct detection of dopamine in sweat, without the need for pretreatment of sweat, and the detection accuracy is comparable to that of the commercial ELISA method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical detection, and in particular relates to a method for preparing an anti-pollution wearable sweat sensor based on a phase transition protein complex hydrogel and its application in quantitatively detecting dopamine in sweat. Background Art

[0002] Wearable devices that monitor health-related biomarkers have broad application prospects in early disease diagnosis and personalized medicine. Among many biological fluids, sweat can be obtained without destroying the skin's protective layer and is easy to collect, so it is classified as a typical non-invasively sampled biological fluid. Studies have shown that sweat contains a variety of biomarkers, such as glucose, uric acid, dopamine, etc. The detection of these markers, like conventional blood tests, can also provide people with important information. Therefore, it is of great significance to develop wearable electrochemical sensors that can monitor markers in sweat in situ.

[0003] However, due to the complex composition of sweat and the low content of markers, the detection process is easily interfered by coexisting biological molecules, which greatly reduces the accuracy and reliability of detection. Although great progress has been made in the research of wearable sweat sensors at home and abroad in recent years, there is still a gap from practical application. The key problems that need to be solved urgently are as follows: (1) Most wearable sensors are rigid. Considering the comfort of human wearing and the requirements for deformation and self-healing ability in practical applications, it is urgent to develop flexible hydrogel materials for wearable devices. (2) Ideal wearable sensors will free clinical testing from the limitations of hospitals or laboratories, and achieve continuous, rapid, and in situ monitoring of a series of health-related physical or chemical parameters through contact with human skin or body fluids. However, proteins, lipids, and bacteria on the skin surface in sweat will form a dirt layer on the electrode surface, causing the sensor function to degrade and significantly affecting the accuracy of detection. Therefore, it is urgent to develop hydrogel materials with good anti-pollution and antibacterial capabilities. (3) Except for conductive polymer hydrogels, most hydrogel materials have poor conductivity and insufficient electrocatalytic ability, resulting in low sensitivity of hydrogel-based electrochemical sensors. Therefore, improving the conductivity and electrocatalytic performance of hydrogels is another difficult problem that needs to be urgently solved in constructing hydrogel-based wearable electrochemical sensors.

[0004] Therefore, developing hydrogel materials with antibacterial, anti-pollution and electrocatalytic properties and constructing practical wearable sweat sensors to detect biomarkers in sweat are issues that technicians in this field need to solve urgently. Summary of the invention

[0005] In view of this, the present invention provides a method for preparing a composite hydrogel material with antibacterial, anti-pollution and electrocatalytic properties and its application in wearable sweat sensors. The present invention is based on an integrated sweat-stimulating printed electrode modified with a composite hydrogel material, which is used for detecting targets in sweat.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The first technical purpose of the present invention is to provide an anti-pollution wearable sweat sensor based on a phase transition protein complex hydrogel, wherein the sensor is based on a self-designed screen-printed electrode that can stimulate sweating and is modified with a phase transition protein complex hydrogel (A-BSA-MX-CeO2 hydrogel); and,

[0008] The self-designed screen-printed electrode that can stimulate sweating consists of two ion introduction (IP) electrodes (cathode and anode) for sweat stimulation, as well as an Ag / AgCl reference electrode, a carbon counter electrode and a carbon working electrode.

[0009] The second technical purpose of the present invention is to provide a method for preparing an anti-pollution wearable sweat sensor based on a phase transition protein complex hydrogel as described above, comprising the following steps:

[0010] I. Preparation of phase transition protein complex hydrogel: The filtered BSA solution (20% w / v), freshly prepared TCEP solution (1 mol / L), CeO2 (6 mg / mL) and MXene (5 mg / mL) were evenly mixed (the final concentrations were 5% w / w, 40 mmol / L, 1.2 mg / mL, 1 mg / mL, respectively), the pH was adjusted to 7.0 and placed at 30°C for one hour to obtain a phase transition protein complex hydrogel (A-BSA-MX-CeO2 hydrogel).

[0011] The pH is adjusted by 5 mol / L sodium hydroxide or 2 mol / L hydrochloric acid, and a certain volume of sodium hydroxide solution or 2 mol / L hydrochloric acid and TCEP solution should be added continuously and quickly.

[0012] II. Preparation of ion introduction (IP) electrodes (cathode and anode): 0.4-1.0 g agarose was dissolved in 10-20 mL PBS buffer solution (0.1-0.2 mol / L, pH 7.0) under stirring conditions, heated at 170°C, and after complete dissolution, cooled to room temperature in a mold to obtain agarose gel and modified it on the positive and negative poles of the IP electrode respectively. Finally, the anode hydrogel was incubated in a 3% pilocarpine nitrate solution for 1 hour.

[0013] III. Assembly of the sensor: The wearable electrode array consists of two ion introduction (IP) electrodes, a carbon working electrode, an Ag / AgCl reference electrode and a carbon counter electrode. Before modifying the working electrode, it was first activated by continuous 40 cycles of CV scanning in 0.1 mol / L, pH 7.4 PBS (scanning range of -0.6-1.6 V, scanning rate of 0.1 V / s). Then, 3 μL of the pre-gelled A-BSA-MX-CeO2 hydrogel solution was dropped on the working electrode, and the composite hydrogel modified interface (A-BSA-MX-CeO2 hydrogel / SPE) was obtained after freeze drying.

[0014] It is worth noting that biofouling caused by non-specific protein and bacterial adsorption is a serious problem faced by electrochemical sensors, which greatly affects the reliability and stability of sensors in real biological samples (such as sweat and urine), and limits the practical application of biosensors in complex biological media. The anti-pollution sensor constructed in the present invention effectively solves the problem of non-specific protein and bacterial adsorption of biosensors in practical applications.

[0015] In particular, proteins, as the basic components of life, are widely used in disease detection and treatment, tissue engineering, etc. due to their high biocompatibility. Protein hydrogels, in particular, perform particularly well. Bovine serum albumin (BSA) is the most abundant protein, which is easy to obtain, low in cost, can minimize the risk of immunogenicity, and is considered to be the cornerstone for making protein-based hydrogels. It is reported that a phase transition protein with good anti-pollution properties can be formed by inducing BSA disulfide reduction by a one-step method at room temperature. In the present invention, the possibility of albumin self-assembly to form a hydrogel was explored for the construction of wearable sensors. Phase transition protein hydrogels were successfully synthesized by adjusting the reducing agent concentration, protein concentration and pH conditions. At the same time, the hydrogel shows excellent anti-pollution properties against a wide spectrum of pollutants, and exhibits strong stability and interfacial adhesion on almost any substrate, making it an ideal anti-pollution flexible material.

[0016] In addition, the introduction of CeO2 and MXene significantly improved the conductivity and electrocatalytic properties of the phase transition protein hydrogel and endowed the composite hydrogel with antibacterial ability. At the same time, the design of the ion introduction electrode met the requirements of sweating on demand and realized the in-situ analysis of sweat.

[0017] The third technical purpose of the present invention is to request protection for the application of a wearable electrochemical sensor prepared by the above preparation method in the quantitative detection of sweat DA.

[0018] The quantitative detection operation is as follows:

[0019] The anti-pollution wearable sweat sensor based on phase-shift protein complex hydrogel was placed in a PBS buffer solution, and different concentrations of the target dopamine DA were added in sequence under magnetic stirring. The amperometric response of the sensor to dopamine DA at 0.3V was recorded to detect the target dopamine.

[0020] The time interval for sequentially adding different concentrations of the target dopamine DA is 20 to 50 seconds.

[0021] Furthermore, the linear detection range of dopamine DA is 0.05-300 μM, and the detection limit is 0.017 μM (S / N).

[0022] The wearable sweat sensor of the present invention can effectively resist biological contamination in actual human sweat samples. When applied to dopamine detection in sweat, the phase transition protein complex hydrogel can not only effectively prevent the adhesion of coexisting proteins, bacteria and other biological molecules on the sensing interface and kill bacteria, but also because the incorporation of CeO2 and MXene has an excellent catalytic effect on dopamine, it effectively improves the detection sensitivity and accuracy of the electrochemical sensor, and it has been verified to have good practical application potential.

[0023] It is worth noting that dopamine DA is one of the important neurotransmitters discovered in the mammalian brain in the 1950s and plays an important role in the central nervous system of biological organisms. Disordered DA levels are closely related to several diseases such as schizophrenia, Parkinson's disease, Alzheimer's disease and euphoria. Therefore, rapid and accurate determination of DA is of great significance for the early diagnosis of these related diseases. The present invention uses dopamine as the target detection object, which is representative to a certain extent.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) Compared with rigid sensor interface modification materials, they are difficult to bend and stretch and cannot fit human skin, so their practical application is extremely poor. The present invention prepares a protein hydrogel with good biocompatibility, flexibility and self-healing properties through a simple one-step method, which greatly improves the practical application ability of wearable devices.

[0026] (2) Most of the existing hydrogel-based electrochemical sensors have the problems of poor conductivity and insufficient electrocatalytic performance. The composite hydrogel of the present invention not only has good antibacterial and anti-pollution properties, but also has good electrocatalytic properties due to the incorporation of conductive materials. At the same time, it is simple to prepare, low in cost, and has a wide range of applicability to substrates.

[0027] (3) Most existing electrochemical sensors cannot be directly used to detect targets in biological fluids. The wearable sweat sensor of the present invention can directly measure dopamine in sweat without pre-treatment of sweat, and has strong practical application capabilities. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0029] Figure 1 This is a schematic diagram of the preparation method of the anti-pollution wearable sweat sensor based on the phase transition protein complex hydrogel of the present invention.

[0030] Figure 2 Atomic force microscopy images of (a) BSA and (b) A-BSA fiber-modified mica sheets provided in embodiments of the present invention.

[0031] Figure 3 Transmission electron microscope images of (a) MXene and (b) CeO2 provided in the embodiments of the present invention, and high-resolution transmission electron microscope image (c) and XRD spectrum (d) of CeO2.

[0032] Figure 4 Transmission electron microscope images and scanning electron microscope images of A-BSA (a, c) and A-BSA-MX-CeO2 hydrogel (b, d) provided in the embodiments of the present invention.

[0033] Figure 5 XPS spectra of A-BSA hydrogel (a) and A-BSA-MX-CeO2 hydrogel (b) provided in the embodiments of the present invention.

[0034] Figure 6 Sweep frequency measurement of the hydrogel provided in the embodiment of the present invention (a), thermogravimetric test of A-BSA-MX-CeO2 hydrogel (b), and repeated water absorption and loss test of A-BSA-MX-CeO2 hydrogel (c).

[0035] Figure 7 The catalytic performance of different modified electrodes provided in the embodiments of the present invention on 1 mM DA in PBS (0.2 mol / L, pH 7.0) solution was tested.

[0036] Figure 8Water contact angle test of different modified electrodes provided in the embodiments of the present invention (a); laser confocal images of bare (b), A-BSA hydrogel (c) and A-BSA-MX-CeO2 hydrogel (d) modified interfaces after immersion in FITC-BSA solution (0.2 mg / mL) for 2 h.

[0037] Fig. 9 The signal suppression rates of different modified electrodes provided in the embodiments of the present invention after being immersed in 100% artificial sweat for different periods of time.

[0038] Fig.10 Live / dead bacteria imaging after incubating Escherichia coli with different modified electrodes provided in the embodiments of the present invention for 24 hours.

[0039] Fig.11 Live / dead bacterial imaging after incubating Staphylococcus aureus with different modified electrodes provided in an embodiment of the present invention for 24 hours.

[0040] Fig.12 Images of Escherichia coli and Staphylococcus aureus plate counting experiments using different modified electrodes.

[0041] Fig.13 Optimization diagram of the experimental conditions of the present invention; (a) Optimization diagram of MXene concentration; (b) Optimization diagram of reaction pH; (c) Optimization diagram of test potential.

[0042] Fig.14 (a) Amperometric response of A-BSA-MX-CeO2 gel / SPE to continuous addition of DA in 0.2 mol / L pH 7.0 PBS at 0.3 V provided in an embodiment of the present invention, the inset is an enlarged view of the curve in the red frame; (b) linear calibration curve of A-BSA-MX-CeO2 gel / SPE, the inset is a partial enlarged view (0.05-10 μmol / L).

[0043] Fig.15 Calibration curves of bare SPE (a), A-BSA gel / SPE (b) and A-BSA-MX-CeO2 gel / SPE (c) provided in the embodiments of the present invention before and after immersion in 100% artificial sweat for 48 hours, and the inset is the amperometric response curve of the corresponding electrode to DA; the ratio of the detection sensitivity (slope of the calibration curve) before and after immersion in 100% artificial sweat for 48 hours (d), asterisk (*) indicates significant difference, P<0.05; asterisk (**) indicates significant difference, P<0.01, one-way analysis of variance.

[0044] Fig.16The amperometric response of the A-BSA-MX-CeO2 gel / SPE provided in the embodiments of the present invention to 50 μM DA and 5 mmol / L glucose (Glu), lactic acid (LA), uric acid (Urea), glycine (Gly) and hydrogen peroxide (H2O2) in 0.2 mol / L pH 7.0 PBS.

[0045] Fig.17 Five independently prepared biosensors provided for the present embodiment were used to detect the amperometric response of 250 μM DA.

[0046] Fig.18 The chronoamperometric response of the sensor provided in an embodiment of the present invention to 50 μM DA before bending (a), after bending inward (b) and outward (c) 15 times. The chronoamperometric response comparison of the sensor to DA before and after bending (d) and the signal retention rate statistics (e).

[0047] Fig.19 The sensor provided in the embodiment of the present invention and the ELISA method are used to analyze real sweat samples. DETAILED DESCRIPTION

[0048] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings of the specification. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] Examples of certain embodiments of the present invention are given below, which are not intended to limit the scope of the present invention.

[0050] In the following examples, the details of instruments and reagents are as follows.

[0051] Equipment: Electrochemical tests were performed on a CHI 660E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.) using a conventional three-electrode system: a platinum wire electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and a bare or modified glassy carbon electrode as the working electrode. The solutions were characterized by fluorescence spectroscopy using a Hitachi FL-4600 fluorescence spectrometer. The interfaces were characterized by scanning electron microscopy using a Hitachi S-4800 scanning electron microscope (Hitachi Co., Japan). The hydrogels were tested by a Zeta potential analyzer (Malvern Technology Co., Ltd., UK). The secondary structure of the phase-transformed BSA formed under different pH conditions was characterized by a circular dichroism (CD) spectrometer. The wettability of the electrode interface was characterized by a JC2000 contact angle instrument (Shanghai Zhongchen Instrument Co., Ltd.). The X-ray diffraction (XRD) pattern of CeO2 nanorods was measured by an X-ray diffractometer (Rigaku Ultima IV) at 45 kV and 40 mA. Thermogravimetric (TG) analysis was from Netzsch Scientific Instruments (Shanghai) Co., Ltd. The freeze drying test was measured by a SCIENTZ-N freeze drying machine of Ningbo Xinzhi Biotechnology Co., Ltd. The mechanical properties of the composite hydrogel were tested at room temperature using an INSTRON3343 universal testing instrument. The rheological properties of the composite hydrogel were measured by a rotational rheometer (TA Instruments-ARES G2) at room temperature.

[0052] Reagents: Accordion-shaped MXene was ordered from Shandong Enyan New Materials Technology Co., Ltd. Tris(2-carboxyethyl)phosphine hydrochloride (TCEP) was ordered from Shanghai Bioengineering Co., Ltd. Ce nitrate hexahydrate (CeN3O9·6H2O, 99.5%), sodium hydroxide (NaOH), and glycine (Gly) were provided by Aladdin Reagent Co., Ltd. (Shanghai, China). Thioflavin-T was provided by Shanghai Sigma Trading Co., Ltd. Bovine serum albumin (BSA), fluorescein isothiocyanate, and dopamine were purchased from Shanghai Adamas Reagent Co., Ltd. Escherichia coli and Staphylococcus aureus were provided by Shanghai Maokang Biotechnology Co., Ltd. SYTO 9 and propidium iodide (PI) were purchased from Beijing Sun Biotechnology Co., Ltd. Lactate, urea, and glucose were ordered from Shanghai Sinopharm Chemical Reagent Co., Ltd. Electrode array (SPE) was provided by Qingdao Botan Technology Co., Ltd. Artificial sweat was purchased from Fuzhou Feijing Biotechnology Co., Ltd. Ultrapure water (18 MΩ / cm) was obtained by a Milli-Q purification system and used for the preparation of all aqueous solutions.

[0053] Example 1

[0054] The construction process of the biosensor is as follows Figure 1 As shown:

[0055] (1) Preparation of composite hydrogel (A-BSA-MX-CeO2 hydrogel): Dissolve 0.2g BSA in 1mL water, wait for complete dissolution and use a 0.2μm filter to prepare a BSA solution, dissolve 0.0287g TCEP in 0.1mL water to prepare a fresh TCEP solution, dissolve 6mg CeO2 nanorods in 1mL water and ultrasonically disperse to prepare a CeO2 nanorod dispersion, and dissolve 5mg MXene in 1mL water and ultrasonically disperse to prepare a MXene dispersion. Take 31μL of water, 25μL of BSA solution, 4μL of TCEP solution, 20μL of CeO2 solution, and 20μL of MXene solution, mix them evenly, and place them at 30°C for one hour to form a composite hydrogel. It is worth noting that the pH during gelation is adjusted by 5mol / L sodium hydroxide or 2mol / L hydrochloric acid. And a certain volume of sodium hydroxide solution or 2mol / L hydrochloric acid and TCEP solution should be added continuously and quickly;

[0056] (2) Preparation of ion electrophoresis (IP) electrode: 0.4 g agarose was dissolved in 10 mL PBS buffer solution (0.1 mol / L, pH 7.0) under stirring conditions, heated at 170°C, and after complete dissolution, cooled to room temperature in a mold to obtain agarose gel and modified it on the positive and negative electrodes of the IP electrode respectively. Finally, the anode hydrogel was incubated in 3% pilocarpine nitrate solution for 1 hour;

[0057] (3) Electrode pretreatment: The electrode array consists of two ion introduction (IP) electrodes, a carbon working electrode, an Ag / AgCl reference electrode and a carbon counter electrode. Before modifying the working electrode, it was first activated by continuous 40 cycles of CV scanning in 0.1 mol / L, pH 7.4 PBS (scanning range of -0.6-1.6 V, scanning rate of 0.1 V / s);

[0058] (4) Assembly of electrochemical sensor: 3 μL of pre-gelled A-BSA-MX-CeO2 hydrogel solution was dropped on the working electrode and freeze-dried to obtain a composite hydrogel modified electrode (A-BSA-MX-CeO2 hydrogel / SPE), i.e., an electrochemical sensor.

[0059] Example 2

[0060] The formation of the phase transition protein fiber (A-BSA) structure has an important influence on the formation of the final hydrogel, so the formation of the phase transition protein fiber was characterized:

[0061] TCEP was used to reduce the disulfide bonds in BSA in one step at room temperature to form phase transition protein fibers, which then formed hydrogels through physical interactions. Atomic force microscopy images verified the formation of phase transition protein fibers. Figure 2As shown, there is no fiber appearance on the BSA modified surface, while there is obvious fiber appearance on the A-BSA modified surface and the fibers cover the mica surface relatively evenly, with an average height of about 2.25 nm.

[0062] Example 3

[0063] Characterization of MXene and CeO2:

[0064] Transmission electron microscopy results show that MXene has a typical layered structure, with each layer arranged in parallel ( Figure 3 a). Figure 3 b shows that the synthesized CeO2 is rod-shaped with an average diameter of about 15nm. In addition, the HRTEM image shows the main crystal plane composition of the CeO2 surface, with the crystal plane spacing of 0.31 and 0.27nm ( Figure 3 c), corresponding to the (111) and (200) planes in the X-ray diffraction (XRD) pattern, respectively. Figure 3 d), demonstrating the successful synthesis of rod-shaped CeO2.

[0065] Example 4

[0066] Characterization of hydrogels:

[0067] The microstructure of the hydrogel was characterized by transmission electron microscopy and scanning electron microscopy ( Figure 4 ). It can be seen from TEM that A-BSA gel ( Figure 4 a) presents a porous network structure; after adding MXene and CeO2, A-BSA-MX-CeO2 gel ( Figure 4 b) The pore structure morphology is well maintained, and the presence of blocky MXene and rod-shaped CeO2 can be clearly seen, proving the successful preparation of the composite hydrogel. In addition, the scanning electron microscope image ( Figure 4 c, d) also demonstrated the successful preparation of the composite hydrogel.

[0068] The chemical compositions of A-BSA hydrogel and A-BSA-MX-CeO2 hydrogel were further analyzed by XPS test. Figure 5 a) and A-BSA-MX-CeO2 hydrogel ( Figure 5 b) The XPS spectra of the modified interface monitored the typical peaks of C1s, O 1s, N1s, S2p, P 2p and Cl 2p. Due to the incorporation of MXene and CeO2, the A-BSA-MX-CeO2 hydrogel modified interface also showed typical peaks of Ti 2p, F 1sCe3d and Ce 4d, proving the successful preparation of the composite hydrogel.

[0069] The solidified state characteristics of the hydrogel were characterized by rheological tests. Figure 6As shown in a, under 1% strain, within the test frequency range of 0.1-10rad / s, the storage modulus (G') and loss modulus (G") remain basically stable, and the storage modulus is always higher than the loss modulus, maintaining a stable gel state. After the incorporation of MXene and CeO2, the storage modulus (G') and loss modulus (G") both increase slightly, and the storage modulus is always higher than the loss modulus, indicating that the incorporation of MXene and CeO2 does not affect the formation of the original hydrogel.

[0070] Due to the presence of BSA hydrophilic groups and the three-dimensional porous network structure formed by cross-linking of phase transition protein fibers, the phase transition protein hydrogel can capture a large amount of water. Thermogravimetric test results show that the water content of A-BSA-MX-CeO2 hydrogel is 84wt% ( Figure 6 b). In addition, after 11 cycles of repeated water absorption and loss, the mass of the hydrogel still remained at 96% of the original mass, indicating that the hydrogel has excellent water retention properties ( Figure 6 c).

[0071] Example 5

[0072] Electrochemical catalytic behavior of dopamine (DA):

[0073] The catalytic performance of the sensing interface was studied by DPV testing, e.g. Figure 7 As shown in the figure, when there is no target, no electrical signal is generated by each modified electrode in 0.2mol / L pH 7.0PBS solution. In the presence of the target DA, SPE generates a catalytic signal. Due to the poor conductivity of protein-based hydrogels, the charge transfer on the electrode surface is significantly inhibited, and the response signal of A-BSA gel / SPE to DA is significantly reduced. The incorporation of MXene makes the catalytic response signal of A-BSA-MX gel / SPE to DA significantly higher than that of A-BSA gel / SPE. The further incorporation of CeO2 further increases the catalytic response signal of A-BSA-MX-CeO2 gel / SPE to DA. Compared with SPE, the response signal is slightly reduced, and the oxidation peak potential is reduced (0.195V), which can meet the detection needs.

[0074] Example 6

[0075] Anti-pollution performance test:

[0076] Hydrophilicity is an important factor affecting the anti-fouling performance of the interface. Excellent hydrophilicity can form a hydration layer on the interface and effectively prevent nonspecific adsorption. Figure 8As shown in a, the modification of A-BSA hydrogel significantly improves the hydrophilicity of the interface, and the water contact angle decreases from 109.0° to 33.7°. The incorporation of hydrophilic MXene further reduces the water contact angle of the A-BSA-MX-CeO2 hydrogel modified interface to 29.2°, which has excellent hydrophilicity.

[0077] The anti-fouling performance of different modified interfaces was qualitatively evaluated by fluorescent protein adsorption test. After immersion in 0.2mg / mL FITC-BSA solution for two hours, a large amount of fluorescent protein was adsorbed on the surface of the bare electrode ( Figure 8 b), while the A-BSA hydrogel modified interface has almost no fluorescence and can well resist the adsorption of nonspecific proteins ( Figure 8 c). Due to the increased hydrophilicity, the A-BSA-MX-CeO2 hydrogel modified interface has almost no fluorescence and has minimal fluorescent protein adsorption ( Figure 8 d), has excellent ability to resist nonspecific protein adsorption.

[0078] The DPV test recorded the changes in electrical signals of different modified interfaces after being immersed in 100% artificial sweat for a period of time (24h, 48h, 72h, 96h). Fig. 9 As shown in the figure, after the bare SPE was immersed in 100% artificial sweat for 48 hours, the signal suppression rate reached 57.9%, and there was a lot of non-specific adsorption. However, after the A-BSA hydrogel modified interface was immersed in 100% artificial sweat for 96 hours, the signal suppression rate was only 13.5%, which has excellent anti-pollution performance. The A-BSA-MX-CeO2 hydrogel modified interface has improved hydrophilicity and anti-pollution performance, and can retain most of the original signal to the greatest extent (the signal suppression rate was only 10.8% after 96 hours of immersion).

[0079] Example 7

[0080] Antibacterial performance test:

[0081] In order to further verify the antibacterial properties of A-BSA-MX-CeO2 hydrogel, different modified interfaces were exposed to Escherichia coli ( Fig.10 ) and Staphylococcus aureus ( Fig.11 ) were incubated at 37°C for 24h, and live / dead bacteria laser confocal imaging was performed after staining with SYTO 9 and PI mixed dyes. Obviously, a large number of live bacteria were adsorbed on the unmodified interface, and only a few live bacteria were adsorbed on the A-BSA hydrogel modified interface due to its excellent antifouling properties. Due to the excellent bactericidal properties of CeO2, only a few bacteria were adsorbed on the A-BSA-MX-CeO2 hydrogel modified interface, and most of them were dead bacteria. The above results show that the A-BSA-MX-CeO2 hydrogel modified interface can effectively reduce the adsorption of bacteria and kill the adsorbed bacteria.

[0082] In addition, the plate counting method was used to detect the colony growth of Escherichia coli and Staphylococcus aureus. 6 CFU mL -1 The modified electrode was immersed in the bacterial solution of Escherichia coli and Staphylococcus aureus for 12 hours, and then rinsed with 1000 μL PBS solution. The PBS bacterial solution after rinsing was mixed with sterile water at a ratio of 1:50 and coated on a surface dish for culture. The results are shown in Fig.12 As shown. The unmodified interface has a large number of colonies growing, and the A-BSA gel modified interface has a small amount of colonies growing due to its excellent anti-fouling performance. The surface modified by the composite hydrogel has almost no colony growth, indicating that the composite hydrogel not only has good anti-bacterial adhesion properties, but can also effectively kill bacteria.

[0083] Example 8

[0084] Optimization of experimental conditions

[0085] In order to obtain the best DA sensing performance, several important experimental parameters (MXene concentration, reaction pH, test potential) were optimized. The optimization diagram of MXene concentration is shown in Figure 2. Fig.13 As shown in a, when the MXene concentration is 1 mg mL -1 The catalytic performance of the sensor to DA reached its best when the concentration was 1 mg·mL, and then tended to be stable. -1 is the optimal concentration of MXene. The optimization diagram of reaction pH is shown in Fig.13 As shown in Figure b, at pH 7.0, the catalytic performance of the sensor for DA is optimal, indicating that protons participate in the reaction, so the detection of DA is pH-dependent. Fig.13 As shown in c, the sensing performance of the sensor to DA under different voltages (the applied potential range is 0.10~0.35V) is characterized by IT test. At 0.3V, the current response reaches the maximum, and this potential is selected as the optimal potential.

[0086] Example 9

[0087] Quantitative detection of dopamine DA

[0088] Under the optimal experimental conditions, the amperometric response signals of the sensor to different concentrations of DA were recorded when DA was continuously added to PBS. Fig.14 a. The sensor showed a good linear relationship with the concentration of DA in the range of 0.05-300 μM (R 2 0.999), and the minimum detection limit was 0.017μM ( Fig.14 b).

[0089] Example 10

[0090] Quantitative Detection of Dopamine DA in Artificial Sweat

[0091] In order to verify the practical application ability of the A-BSA-MX-CeO2 hydrogel modified interface, the amperometric response signals of different modified interfaces to the continuous addition of DA were recorded before and after immersion in 100% artificial sweat for 48 hours. Fig.15 As shown, SPE( Fig.15 a) After immersion in 100% artificial sweat for 48 hours, obvious changes in the current response signal appeared. In contrast, A-BSA gel / SPE ( Fig.15 b) and A-BSA-MX-CeO2 gel / SPE( Fig.15 c) There is no significant change in the response signal to DA after treatment with artificial dry liquid. Fig.15 d, the sensitivity ratios of SPE, A-BSA gel / SPE and A-BSA-MX-CeO2 gel / SPE before and after immersion in artificial sweat were 69.6%, 89.6% and 92.6%, respectively, indicating that A-BSA gel and A-BSA-MX-CeO2 gel have good anti-pollution properties in complex biological fluids, showing great practical application capabilities and detection accuracy.

[0092] Embodiment 11

[0093] Selectivity, reproducibility and stability of antifouling sensors based on composite hydrogels

[0094] Other non-target substances coexisting in human sweat may interfere with the detection of the target, resulting in poor detection accuracy. Therefore, substances such as lactic acid (LA), glucose (Glu), urea, and sodium chloride, which are common in human sweat, were selected as interfering substances to test the selectivity of the DA sensor. Fig.16 As shown in the figure, even when the concentration of the interferent is 100 times that of the target DA, no obvious amperometric response is detected, indicating that the sensor has excellent selectivity. In addition, the amperometric response signals of 5 independently prepared A-BSA-MX-CeO2 gel / SPE to 250μM DA were tested ( Fig.17 ), the results showed that the sensor had satisfactory reproducibility (RSD = 4.08%).

[0095] Example 12

[0096] Mechanical stability characterization of wearable sensors

[0097] As a wearable sensor, it is often subjected to various deformations caused by human body movements, so it needs to have elasticity against mechanical stress. In order to verify the feasibility of the prepared wearable sensor in practical applications, its bending deformation stability was tested. The chronoamperometric response of the sensor to 50μM DA was tested before bending (18a), inward (18b) and outward (18c) 15 times. The results showed that repeated inward and outward bending had no significant effect on the electrochemical properties of the sensor (18d, e), confirming that the sensor has strong mechanical stability under various deformations.

[0098] Embodiment 13

[0099] Actual sample testing

[0100] The prepared sensor was used to measure DA in 5 actual sweat samples, and the results were compared with the commonly used ELISA method to evaluate the application ability of the wearable sensor in actual sample detection. Fig.19 As shown, the measurement results of the two methods are basically consistent, and the difference is less than 7%, indicating that the sensor has satisfactory accuracy for actual sample detection.

[0101] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An anti-pollution wearable sweat sensor based on phase transition protein complex hydrogel, characterized in that: The sensor is based on a screen-printed electrode that can stimulate sweating and is modified with a phase transition protein complex hydrogel; the phase transition protein complex hydrogel is an A-BSA-MX-CeO2 hydrogel; and, The screen-printed electrode capable of stimulating sweating is composed of two ion introduction (IP) electrodes for sweat stimulation, an Ag / AgCl reference electrode, a carbon counter electrode and a carbon working electrode; The method for preparing the anti-pollution wearable sweat sensor based on phase transition protein complex hydrogel comprises the following steps: I. Preparation of phase transition protein complex hydrogel: After uniformly mixing BSA solution, TCEP solution, CeO2 and MXene, adjusting the pH and standing to obtain phase transition protein complex hydrogel; II. Preparation of ion introduction (IP) electrode: agarose was dissolved in PBS buffer solution under stirring conditions, heated until completely dissolved, and then cooled to room temperature in a mold to obtain agarose gel, which was then modified on the cathode and anode of the IP electrode respectively; and the anode hydrogel was cultured in pilocarpine nitrate solution for several hours; III. Preparation of wearable sensors: The wearable electrode array consists of two ion introduction (IP) electrodes, a carbon working electrode, an Ag / AgCl reference electrode and a carbon counter electrode. Before modifying the working electrode, the electrode was activated by continuous 40 cycles of CV scanning in PBS, and then the A-BSA-MX-CeO2 hydrogel solution before standing was dropped on the working electrode to form a hydrogel, and freeze-dried to obtain a composite hydrogel modified interface. The fibers of the phase transition protein complex hydrogel are cross-linked to form a three-dimensional porous network structure.

2. The method for preparing the anti-pollution wearable sweat sensor based on phase transition protein complex hydrogel according to claim 1, characterized in that: The specific method of step I is: 20% w / v BSA solution, 1 mol / L TCEP solution, 6 mg / mL CeO2 and 5 mg / mL MXene were uniformly mixed to respective concentrations of 2-10% w / v, 10-100 mmol / L, 1.0-2.0 mg / mL, 0.5-2.0 mg / mL, adjusted to pH 7.0 and placed at 30°C for one hour to obtain a phase transition protein complex hydrogel; The pH is adjusted by 5 mol / L sodium hydroxide or 2 mol / L hydrochloric acid, and the sodium hydroxide solution or hydrochloric acid and TCEP solution should be added continuously and quickly.

3. The method for preparing the anti-pollution wearable sweat sensor based on phase transition protein complex hydrogel according to claim 1, characterized in that: The specific method of step II is: Dissolve 0.4-1.0g agarose in 10-20mL PBS buffer solution under stirring conditions, heat at 170°C, and after complete dissolution, cool to room temperature in a mold to obtain agarose gel and modify it on the positive and negative electrodes of the IP electrode respectively; incubate the anode hydrogel in 3% pilocarpine nitrate solution for 1 hour; The PBS buffer solution has a concentration of 0.1-0.2 mol / L and a pH of 7.

0.

4. The method for preparing the anti-pollution wearable sweat sensor based on phase transition protein complex hydrogel according to claim 1, characterized in that: The specific method of step III is: Before modifying the working electrode, it was first activated by continuous 40 cycles of CV scanning in 0.1 mol / L, pH 7.4 PBS. Then, 3 μL of the pre-gelled A-BSA-MX-CeO2 hydrogel solution was dropped on the working electrode and freeze-dried to obtain a composite hydrogel-modified interface. The CV scan range is -0.6-1.6 V, and the scan rate is 0.1 V / s.

5. Application of the anti-pollution wearable sweat sensor based on phase transition protein complex hydrogel as claimed in claim 1 in sweat detection.

6. The use according to claim 5, characterized in that: Including for quantitative detection of dopamine DA in sweat, the quantitative detection is: The anti-pollution wearable sweat sensor based on phase transition protein complex hydrogel was placed in PBS buffer solution, and different concentrations of the target dopamine DA were added in sequence under magnetic stirring. The amperometric response of the sensor to dopamine at 0.3V was recorded to detect the target dopamine. The time interval for sequentially adding different concentrations of the target dopamine DA is 20 to 50 seconds.

Citation Information

Patent Citations

  • Electrochemical sensor as well as preparation method and application thereof

    CN115201302A

  • Flexible wearable sweat electrochemical sensor, sweat monitoring method and application

    CN115586230A

  • Composite hydrogel, integrated micro electrochemical sensor, detection method and application

    CN117844067A